Toxoplasmose silvestre: detecção de anticorpos Anti-Toxoplasma gondii em veados-campeiros (Ozotocerus bezoarticus) e cervos do pantanal (Blastocerus dichotomus) naturalmente infectados - Ferreira, Ronize Andréia (1997)
Serum samples from 107 cervids were examined for Toxoplasma gondii antibodies by using four serological tests: indirect hemagglutination (IHA), indirect immunofluorescence (IFA), dot-enzyme linked immunosorbent assay (dot-ELISA) and enzyme-linked immunosorbent assay (ELISA). Part of these samples (38%) were obtained from pampas deer (Ozotocerus bezoarticus) living at Pantanal region and Emas National Park, Brazil. The remaining samples (62%) came from marsh deer (Blastocerus dichotomic) living at Tietê river course, Brazil. Taken into account that the samples were considered positive when showing reactivity in at least two tests, the global prevalence o f antibodies anti-77. gondii was found in 23 out of 107 cervids (21,50%). By IHA, 13.08% o f the deer serum samples had titers from 16 to 2048. By IF A, 21.49% had titers from 8 to 512, while 19.63% of the serum samples had detectable antibodies by dot-ELISA, with titers ranging from 8 to 128. By ELISA, 28.97% had titers from 16 to 256. The highest prevalence of Toxoplasma gondii antibodies was found in subadults (32.08%), following by adults (26.98%) and juveniles (13.33%). Only one serum sample (8.33%) from infant deer was positive in the serological tests. These findings are consistent with the hypothesis that points out the existence of natural infection of these cervid populations by Toxoplasma gondii in those studied regions